The Impact of Reported Beta-Lactam Allergy in Hospitalized Patients with Hematologic Malignancies Requiring Antibiotics - Huang, Kuan-Hsiang Gary; Cluzet, Valerie; Hamilton, Keith; Fadugba, Olajumoke (Clinical infectious diseases, 2018)
Patients hospitalized with hematologic malignancy are particularly vulnerable to infection. The impact of reported beta-lactam (BL) allergy in this population remains unknown. To define the impact of reported BL-only allergy (BLOA) label on clinical outcomes compared to those with no BL allergy (NBLA) in hematologic malignancy inpatients requiring systemic antibiotics. Retrospective cohort study of adult inpatients with hematologic malignancy admitted at two tertiary care hospitals 2010-2015. The primary outcome was hospital length of stay (LOS) after first antibiotic. Secondary outcomes included re-admission, mortality, complications, total hospital charges, and antibiotic usage. In our cohort (n=4671), 38.3% had leukemia, 4.9% had Hodgkin's lymphoma, 36.1% had non-Hodgkin's lymphoma and 20.7% had multiple myeloma. Among subjects, 35.1% reported antibiotic allergy, 14.1% (n=660) had BLOA (including 9.3% with penicillin-only allergy and 3.3% cephalosporin-only allergy). Subjects with BLOA had longer median LOS compared to NBLA (11.3 vs. 7.6 days, p<0.001), which remained significant after multivariable adjustment. Patients with BLOA also had significantly worse outcomes compared to NBLA in terms of mortality rate at 30-days (7.6% vs. 15.8%, p=0.017) and 180-days (15.8% compared to 12.2%, p=0.013), 30-day re-admission rate (19.2% vs. 15.1%, p=0.008), Clostridium difficile rate (17.7% vs. 11.6%, p<0.001), total hospital charges ($223046 vs. $173256, p<0.001), antibiotic classes used (median 3 vs. 2 classes/patient, p<0.001), and antibiotic duration (median 9.0 vs. 6.0 days, p<0.001). In hospitalized patients with hematologic malignancy requiring antibiotics, patients with reported BL allergy have worse clinical outcomes and higher healthcare cost than those without BL allergy label.